Digital Storytelling and the Promotion of Community-Led Development Initiatives in Urban Slums - Uduak Imoh Udoudom; Ifeanyi Martins Nwokeocha (MultiTech Publisher, 2023)
This conceptual research explores the potential of digital storytelling in promoting community-led development initiatives in urban slums. The conceptual research examines the impact of using digital storytelling platforms and processes as tools for community engagement and empowerment, and how they contribute to the promotion of sustainable development practices in those communities. To achieve its objectives, the study focuses on case studies from several cities in the Global South, where community-based organisations and Non-Governmental Organisations (NGOs) have used digital storytelling to raise awareness about the social, political, economic and environmental conditions in slums; advocate for policy reform as well as promote community-led solutions to poverty, violence, and environmental degradation. The findings of the study suggest that digital storytelling formats and processes are effective means of engaging diverse stakeholders in urban development, generating new knowledge and perspectives, and fostering participatory decision-making processes that empower slum dwellers to shape their own future. However, the paper also identifies several challenges and limitations associated with digital storytelling, including issues of representation, power asymmetries, and sustainability.